2016
DOI: 10.1016/j.jad.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral whole blood microRNA alterations in major depression and bipolar disorder

Abstract: Major depression (MD) and bipolar disorder (BD) are severe and potentially life-threating mood disorders whose etiology is to date not completely understood. MicroRNAs (miRNAs) are small non-coding RNAs that regulate protein synthesis post-transcriptionally by base-pairing to target gene mRNAs. Growing evidence indicated that miRNAs might play a key role in the pathogenesis of neuropsychiatric disorders and in the action of psychotropic drugs. On these bases, in this study 1 These authors contributed equally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(87 citation statements)
references
References 48 publications
2
84
0
1
Order By: Relevance
“…Previous studies have implicated the altered expression of let-7f-5p in several diseases, including major depression, myasthenia gravis, Alzheimer's disease (40)(41)(42), and neoplastic conditions, including laryngeal carcinoma, CRC and thyroid cancer (43,44). Notably, Pathak et al (45) reported that let-7f-5p was highly upregulated in the human colon cancer HCT116 and SN38 cell lines following radiation treatment in a p53-directed manner, indicating that let-7f-5p may contribute to the chemoresistance of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated the altered expression of let-7f-5p in several diseases, including major depression, myasthenia gravis, Alzheimer's disease (40)(41)(42), and neoplastic conditions, including laryngeal carcinoma, CRC and thyroid cancer (43,44). Notably, Pathak et al (45) reported that let-7f-5p was highly upregulated in the human colon cancer HCT116 and SN38 cell lines following radiation treatment in a p53-directed manner, indicating that let-7f-5p may contribute to the chemoresistance of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…While to role of miRNAs has largely been studies in cells, miRNAs can also readily be found in the blood. Furthermore, stress-related disorders such as PTSD and major depression are associated with changes in blood-borne miRNA [47, 48] and intracellular tissue miRNA are changed by stressor exposure [4952]. Because naked circulating miRNAs are degraded quickly in the bloodstream, most blood-borne miRNA are bound to protective proteins, such as high density lipoprotein and argonaute protein [53, 54], or packaged into protective microvesicles, such as exosomes [26, 27].…”
Section: Regulation Of Stress-induced Sterile Inflammation: Mirna Andmentioning
confidence: 99%
“…miRNAs, which are short, noncoding sequences that typically regulate gene expression by suppressing protein coding mRNA, have been demonstrated to be biomarkers for several psychological disorders, including schizophrenia, major depressive disorder, and bipolar disorder (Kichukova, Popov, Ivanov, & Vachev, 2016; Maffioletti et al, 2016; Schmidt, Keck, & Buell, 2015). Within the central nervous system, miRNA are considered to play a major role in gene expression regulation (Kuss & Chen, 2008; Martinetz, 2016); however, the specific role of miRNAs in PTSD remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%